2009
DOI: 10.1523/jneurosci.3437-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Organization of Multisensory Responses in Temporal Association Cortex

Abstract: Neurons in sensory cortices are often topographically organized according to their response preferences. We here show that such an organization of response preferences also exists in multisensory association cortex. Using electrophysiological mappings, we probed the modality preference to auditory and visual stimuli of neurons in the superior temporal association cortex of nonhuman primates. We found that neurons preferring the same modality (auditory or visual) often co-occur in close spatial proximity or occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
94
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 48 publications
13
94
1
Order By: Relevance
“…Across neurons, responses to audiovisual stimuli were stronger than responses to unisensory auditory or visual stimuli [Dahl et al (2009) Recording both auditory and visual unimodal units along a single penetration was significantly less likely in the actual data than in randomized data, in which all units were randomly assigned to individual penetrations; in contrast, penetrations with only bimodal units were significantly more likely in actual data than in randomized data [Dahl et al (2009)…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…Across neurons, responses to audiovisual stimuli were stronger than responses to unisensory auditory or visual stimuli [Dahl et al (2009) Recording both auditory and visual unimodal units along a single penetration was significantly less likely in the actual data than in randomized data, in which all units were randomly assigned to individual penetrations; in contrast, penetrations with only bimodal units were significantly more likely in actual data than in randomized data [Dahl et al (2009)…”
mentioning
confidence: 95%
“…The recent study by Dahl et al (2009) in The Journal of Neuroscience is the first successful attempt to use a stimulusdriven electrophysiological approach to address this question. Recordings of singleunit and multiunit activity within the midportion of the uSTS in rhesus monkeys in the presence of auditory, visual, or audiovisual stimuli, revealed that neurons responding to a single modality often were close to neurons having the same modality preference and to bimodal neurons.…”
mentioning
confidence: 99%
See 3 more Smart Citations